Respuesta :
Answer:
- [tex]\frac{1}{2}[/tex]
Step-by-step explanation:
Substitute the given values into the equation and evaluate
v = 2 + (- 5 × [tex]\frac{1}{2}[/tex])
= 2 - [tex]\frac{5}{2}[/tex]
= [tex]\frac{4}{2}[/tex] - [tex]\frac{5}{2}[/tex] = - [tex]\frac{1}{2}[/tex]
Answer: [tex]\bold{v=-\dfrac{1}{2}}[/tex]
Step-by-step explanation:
v = u + at
Substitute u = 2, a = -5 , t = [tex]\dfrac{1}{2}[/tex]
[tex]v=(2)+(-5)(\dfrac{1}{2})\\\\\\.\ =2 - \dfrac{5}{2}\\\\\\.\ =2\bigg(\dfrac{2}{2}\bigg)-\dfrac{5}{2}\qquad \text{need a common denominator to add fractions}\\\\\\.\ =\dfrac{4}{2}-\dfrac{5}{2}\\\\\\.\ =\boxed{-\dfrac{1}{2}}[/tex]